Resonating Electrostatically Guided Electrons - Seidling, Michael; Schmidt-Kaler, Franz; Zimmermann, Robert; Simonaitis, J. W.; Keathley, P. D.; Berggren, Karl K.; Hommelhoff, Peter (Physical Review Letters, 2024)
An essential component for quantum-enhanced measurements with free electrons is an electron resonator. We report stable guiding of free electrons at 50 eV energy for up to seven round trips in a linear autoponderomotive guiding structure, which is realized with two microstructured printed circuit boards that generate the required electromagnetic fields. Free electrons are laser triggered from a sharp tungsten needle tip and coupled in at the front of the electron resonator with the help of sub-nanosecond-fast switchable electron mirrors. After a variable time delay, we open the rear electron mirror and measure the number of trapped electrons with a delay-line detector. We demonstrate, simulate, and show ways of optimizing an electron resonator in simulations, which will help enable “interaction-free” measurement setups, including multipass and quantum-Zeno effect based schemes, helping to realize the quantum electron microscope.<br